Jüdischer Widerstand in Europa (1933-1945) Formen und Facetten - Schoeps, Julius H.; Bingen, Dieter; Botsch, Gideon (Europäisch-jüdische Studien - Beiträge, 2016)
With courage born of desperation, Jewish fighters began their resistance in April 1943 in the Warsaw ghetto. This was the best known but only one of many Jewish resistance activities against the National Socialist policy of annihilation. This volume addresses the different forms and facets of Jewish resistance, such as the partisan war, underground movements, camp uprisings, assistance for escapes, and cultural resistance.